2003
DOI: 10.1007/s00113-003-0596-7
|View full text |Cite
|
Sign up to set email alerts
|

Operative vs. konservative Therapie der vorderen Kreuzbandruptur: eine systematische Literatur�bersicht

Abstract: The aim of this paper was to examine all studies that compared operative and conservative treatment of anterior cruciate ligament (ACL) rupture. Covering a period of 22 years all relevant articles were retrieved from the medical databases Medline, Embase, and Cochrane. The results of these studies were judged on to the criteria of subjective stability (giving-way phenomenon), objective stability (pivot shift test), and return to the preinjury level of sports. There were 11 different studies published in 16 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
0
13
0
3
Order By: Relevance
“…The specificity of the Lachman test is 92% (95% CI, 88-94) for the studies with the highest methodological quality 9,12,39,60,69 and 95% (95% CI, 93-96) when excluding these studies. The pivot shift test shows a sensitivity of 20% (95% CI, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for the studies with the highest methodological quality 9,18,55,60,69 and 25% (95% CI, 21-28) for the rest of the studies with lower methodological qualities. The difference between the specificities is just 1%, showing 97% (95% CI, 95-99) for the studies with the highest methodological quality 9,55,60,69 and 98% (95% CI, 96-100) when excluding these studies.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of the Lachman test is 92% (95% CI, 88-94) for the studies with the highest methodological quality 9,12,39,60,69 and 95% (95% CI, 93-96) when excluding these studies. The pivot shift test shows a sensitivity of 20% (95% CI, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for the studies with the highest methodological quality 9,18,55,60,69 and 25% (95% CI, 21-28) for the rest of the studies with lower methodological qualities. The difference between the specificities is just 1%, showing 97% (95% CI, 95-99) for the studies with the highest methodological quality 9,55,60,69 and 98% (95% CI, 96-100) when excluding these studies.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…51 Based on a recent literature meta-analysis, ACL reconstruction seems to be superior to conservative treatment to resolve objective and subjective joint instability and help the return to preinjury level of sports. 29 From this perspective, it is of fundamental importance to perform the most accurate tests available to diagnose an ACL rupture, particularly for physical therapists that practice in a sports and orthopaedic setting without a referral by a physician. They rely heavily on clinical tests and therefore need to be able to screen for ACL injury to make appropriate treatment decisions and to make referral for further imaging and diagnosis and possible surgery.…”
mentioning
confidence: 99%
“…1 During the last 20 years the majority of published articles have agreed that operative reconstruction is the accepted method to treat the acute complete ACL rupture. 2,3,4,5 On the other hand, several authors commented that there were higher osteoarthritis rates in knees after operative ACL reconstruction than in nonoperated knees. 6,7,8,9 Diekstall et al 10 showed significantly higher satisfaction levels and better results in subjective scores in conservatively treated patients.…”
mentioning
confidence: 95%
“…Evidence based medicine · Orthopedic surgery · Review · Critical appraisal · Decision making Operation ausreichend begründen [2,23]: Die Sportfähigkeit wird unter konservativer Therapie in rund 30% der Fäl-le wieder erreicht, unter operativer Therapie in rund 60%.…”
Section: Introductionunclassified